Investigating nonflow contribution on elliptic flow in p-Pb collisions with the AMPT model - Yu, Ning; Zhang, Zuman; Zhang, Meimei (Frontiers in Physics, 2025)
This study investigates the subtraction of nonflow contributions in heavy-ion collisions using the multiphase transport (AMPT) model, focusing on unidentified charged trigger particles and various species of charged associated particles, including pions, kaons, protons, and antiprotons. The analysis centers on elliptic flow (v2) measurements in proton-lead (p-Pb) collisions at a center-of-mass energy of sNN=5.02 TeV, within the transverse momentum range of 0.3<pT<4 GeV/c. We aim to evaluate the influence of nonflow sources, such as jet correlations and resonance decays, particularly in small collision systems. To reduce nonflow effects, we subtract the per-trigger yield distribution from peripheral p-Pb or proton-proton collisions at the same energy. Our results indicate that nonflow contributions in central collisions exhibit minimal dependence on the subtraction of per-trigger yields from peripheral p-Pb or pp collisions. We can find the second-order coefficients for pions and kaons are comparable, while v2p is smaller at low pT and larger at high pT compared to v2π, with a crossing observed around 2 GeV/c. A comparison with experimental data from p-Pb collisions at sNN=5.02 TeV is also presented. PACS 25.75. LdCollective flow ⋅ 24.10. LxMonte Carlo simulations (including hadron and parton cascades and string breaking models).